Integrity, Education, and Moral Renewal – International Insights and Lessons for Hungary - Biró, Ferenc Pál (Public Finance Quarterly, 2025)
The scandal that broke out in Brazil in 2014 came to be known in the media as “Lava Jato” – or “Car Wash”. What began as a money laundering case centred around a small car wash quickly escalated into one of the largest corruption scandals on the continent. The investigation uncovered a multi-billion-dollar bribery network that had been operating for decades around Petrobras, a state-owned oil company. Politicians, state officials, as well as multinational companies and criminal networks were all involved. The mechanism was deceptively simple – yet devastating: large corporations were awarded overpriced contracts by the state-owned oil company, with part of the surplus ending up in the pockets of political parties and decision-makers. The machinery of corruption served not only to enrich certain individuals, but also to finance the maintenance of the entire political system. The consequences were staggering: Petrobras’s share price collapsed, tens of thousands of jobs were lost, and Brazil’s economy plunged into a deep recession. Ministers, members of government, party leaders and executives from the largest construction company were all imprisoned, and even Luiz Inácio Lula da Silva, the country’s iconic former president, stood trial. The social fabric of the country was shaken, as millions of people took to the streets, having lost their trust in the political and economic elite. Yet the true tragedy of the Lava Jato scandal went far beyond financial loss or the exposure of the political elite, as the people of Brazil came to realise that corruption is not the sin of a few “black sheep”, but a systemic driving force that permeates everything. The erosion of trust has left a lasting wound on society that will affect generations to come. One of the most shocking revelations of this scandal was the sheer scale of the bribes involved. Investigators found that construction companies had inflated project costs by up to 20%, not only funnelling billions of dollars into secret political funds, but also showering politicians and corporate executives with luxury beachfront apartments in Rio, yachts, Rolex watches, and suitcases full of cash. The blend of multi-billion-dollar contracts and extravagant personal gifts turned the scandal into a symbol of how systemic corruption can simultaneously rot institutions and corrode personal integrity – all while affording a life of luxury to a select few.